The book of lies - Meltzer, Brad (Houdder & Stoughton, 2008)
In 1932, Mitchell Siegel was killed by three gunshots to his chest. While mourning, his son dreamed of a bulletproof man and created the world's greatest hero: Superman. And like Cain's murder weapon, the gun used in this unsolved murder has never been found. Until now. Today in Fort Lauderdale, Florida, Cal Harper comes face-to-face with his family's greatest secret: his long-lost father, who's been shot with a gun that traces back to Mitchell Siegel's 1932 murder. But before Cal can ask a single question, he and his father are attacked by a ruthless killer tattooed with the anicent markings of Cain. And so begins the chase for the world's first murder weapon. What does Cain, history's greatest villain, have to do with Superman, the world's greatest hero? And what do two murders, committed thousands of years apart, have in common?